Innovative vibriosis control in open aquaculture: Paratapes undulata as a sustainable growth and resistance enhancer in red tilapia - Rehab E. Mowafy; Hend M. Megahed; Sally H. Abou Khadra; Mohamed A. Bakry; Ahmed Hussien Moustafa; Azza SalahEldin El-Demerdash (Scientific Reports)
Abstract This study demonstrates the novel therapeutic potential of Paratapes undulata for mitigating Vibrio alginolyticus infection in red tilapia. In vivo, P. undulata significantly improved growth by approximately 362% in group G3 (Clam-treated Control) and 284% in group G4 (Clam-treated Infected), compared to the infected control group (G2), and reduced mortality by 100% in group G3 and 75% in group G4, compared to the infected control group (G2), and alleviated clinical signs, correlating with enhanced hematological and biochemical profiles, and reduced tissue damage. Mechanistically, P. undulata modulated the immune response by shifting cytokine balance towards anti-inflammation, enhanced antioxidant capacity, and directly inhibited Vibrio alginolyticus virulence. Gas Chromatography–Mass Spectrometry and Fourier-Transform Infrared Spectroscopy analyses revealed the presence of bioactive compounds contributing to these effects. These findings establish P. undulata as a promising, natural, and sustainable biocontrol agent for vibriosis in aquaculture, offering a novel strategy for disease management and reducing reliance on antibiotics. This study suggests that P. undulata can be effectively incorporated into aquaculture feed or water treatments to prevent and manage vibriosis outbreaks.